A search for a curriculum framework for setting an Islamic school in Uzbekistan : benchmarking of two Islamic schools in Malaysia - Uralova, Kamola (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Thereview of relatedliterature on the subject reveals that the traditional teaching methods in madrasas, masjids, and Islamic institutions in Uzbekistan are still being preserved by a minority of Uzbek youth. These madrasas and masjids produce only ustadh, ustadha, or teachers in their communities but are unable to contribute to the society in other fields such as economy, politics, and also help in solving current global issues. Moreover, the public school system has also failed to prepare the Uzbek Muslim youth for a balanced life and to preserve their faith in Allah (SWT) due to having only secular subjects in the curriculum. Hence, the main purpose of this study is to compare two Islamic schools as standards or benchmarks for Islamic schools of Uzbekistan. The qualitative method, namely using a case study of the administrators and teachers of two schools, includes interview and the use of curriculum criticism which compares and contrasts the curricula of the chosen two Islamic schools of Malaysia. The data were collected through the semi-structured interview and documents which both Islamic schools provided. Findings of the study include analyses and discussions of the philosophy, principles, core values, vision and mission of the two Islamic schools; Islamic ethos in the school environment; the Islamic Integrated Curriculum; teaching and assessment methods for Islamization, integration of values, and motivating students' interests in acquiring knowledge; and finally, suggestions for the best possible design of a curriculum framework for an Islamic school in Uzbekistan.The study found that both Islamic schools of Malaysia have already taken the initial step of implementing the Islamic Integrated Curriculum which is highly discussed and demanded by many contemporary Muslim scholars in order to prepare the ummah to be in tandem with the dramatic changes of the 21st century. This research therefore suggests that curriculum integration in an education system must be implemented in order to deliver a holistic Islamic education and this includes the case for modern Uzbekistan education system.